Photovoltaic power supply technology and electricity saving strategies for fixed-velocity-measuring system - Li Jian (Dianzi Jishu Yingyong, 2022)
The electric power supply methods for fixed-velocity-measuring system(FVMS) based on PV technology are proposed after analysis and comparison among the current methods for FVMS on freeway. According to the sunshine condition in typical low sunshine areas, all components consist of PV system are specially designed, including the related maximum power point track(MPPT) technology for solar panel and the charge-discharge algorithm for storage battery in the controller. Targeted electricity saving strategies for FVMS on freeway are put forward. Experimental results show high efficiency and stability of the dedicated controller and in practical application, the specially designed PV system in this paper can provide continuous electric power supply throughout a year in an efficient way, and the output voltage and frequency are steady.